ผลของโปรแกรมการส่งเสริมสมรรถนะแห่งตนและการสนับสนุนจากครอบครัว ต่อพฤติกรรมส่งเสริมสุขภาพของผู้ป่วยสูงอายุโรคต้อหิน - หทัยกาญจน์ เชาวกิจ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purpose of this quasi-experimental research was to examine the effect of self- efficacy and family support enhancement program on health promoting behaviors among glaucoma disease elderly patients. Self-efficacy Theory of Bandura (1997) and Social-support Theory of House (1981) were used as the conceptual framework. The subjects comprised of 60 elderly patients with glaucoma disease at Glaucoma clinics, King chulalongkorn Memorial Hospital of the Thai Red Cross Society, which devided 30 as a control group and another 30 was experimental group. Sex, education, salary and disease were matched. The Control group received the regular health teaching and the experimental group received the self- efficacy and social support enhancement program, which consisted of physiological assessment and affective states stimulation, verbal persuasion, vicarious experiences and enactive mastery experiences, Family support consisted of emotional support, appraisal support, informational support and instrumental support. Health promoting behaviors was accessed using a modified version of the questionnaire developed by Suchada (1999) by using Pender’s Health promoting Model (1996). The instruments were tested for their internal consistency using Cronbranch’s alpha. The demonstrated acceptable reliability at .84. Data were analyzed using mean, standard deviation, paired-t test and repeated measures ANOVA statistics. Major findings were as follows: 1. The mean score of health promoting behaviors elderly patients with glaucoma disease in the experimental group receiving self-efficacy and family support enhancement program was significantly higher than that before receiving perceived benefit promoting program (p<.05). 2. The mean score of health promoting behaviors elderly patients with glaucoma disease in the experimental group receiving self-efficacy and family support enhancement program was significantly higher than that of the control group (p<.05).